(untitled) (Fiep Bulletin - online, 2013)
This study stemmed from the experience of Cinoterapia - facilitated by therapy dogs for therapeutic or educational purposes, an interdisciplinary approach with a group of disabled children’s APAE of São Gonçalo, held with the institution’s partnership with the Kennel of the Military Police of that city . Kennel was possible through the cooperation and guidance of a veterinarian, the drivers / trainers and dogs, properly selected and trained, for therapeutic intervention in processes. This study aims to describe the design of Cinoterapia held in APAE of São Gonçalo, considering the human development and the human / animal. To that end, base ourselves on the theory Bioecologico Human Development, proposed by Bronfenbrenner that is justified by the potential that the theory has to explain inseparable from the person in development and the contexts in which it falls. The Paradigm Bioecologico highlights four inter-related clusters that are in constant interaction: person - process - context - time. Participated in this study, a group of 30 students from 4 to 16 years with disabilities (Cerebral Palsy with Intellectual Disabilities), and with inadequate responses to stimuli. As a tool for the collection of information, used three sheets Rating: (Functional Independence Evaluation, Assessment and Evaluation of Daily Note Responsible) and Reporting, made in the institution by an interdisciplinary team. In general, living together with dogs stimulates responsibility, improves self-esteem, the self and provides a closer, or even the realization of social relationships as they facilitate the physical contact and verbal. Through the dog can induce a degree of motivation that will enable a better biopsychosocial development. The professional uses the dog as a mediator of this process, because even the most resilient of individuals, is uneasiness in the presence of the dog and thereby diminish their defenses facilitating the therapeutic action.